Designing a flutter-based community recipe mobile application - Nik Ahmad Uzair; Zarina Che Embi (Institute of Advanced Engineering and Science, 2026)
This study focuses on developing a cross-platform mobile application for community-based recipe sharing, addressing the increasing role of mobile technology in daily life. Although recipe apps are globally popular, their adoption in Malaysia remains limited. The proposed application aims to fill this gap by providing users an interactive platform to explore, share, and try new recipes within a cooking-focused community. Key features include personalized recipe suggestions, and an intuitive, easy-to-use interface designed for all devices, enhancing user engagement and promoting community interaction. A background study is conducted to understand the existing landscape and user needs. It is followed by a design phase, which will lay the groundwork for addressing the identified challenges. Based on the insights gained from the background study and design outline, a mobile application is developed, aligning with the analyzed requirements and system design. This paper reports on the design and usability evaluation of this study. Based on the design guidelines, it has been found that this application could provide an intuitive and seamless user experience. Future works include the integration of smart kitchen features and personalized machine learning for better user experience.